The relationship between the simultaneity present of cagA and hopQI genes in Helicobacter pylori and the risk of gastric cancer - Chen, Baosheng; Zhang, Jishui; Ma, Qiutong (Cellular and Molecular Biology, 2021)
Helicobacter pylori is a bacterium that causes infections in the gastrointestinal tract. This type of bacterium is very common and contagious at the same time. H. pylori enters the mouth and continues its course along the gastrointestinal tract. H. pylori infection induces an inflammatory response that leads to the activity of neutrophils, lymphocytes, plasma cells, and macrophages. In addition to the bacterial role in gastric mucosa, the host’s inflammatory response may also play a role in disease outcome. In inflammation, the risk of carcinogenesis increases due to DNA damage increased proliferation and the creation of an environment rich in cytokines and growth factors. Genetic methods and diagnosis of H. pylori genes are used to identify healthy and healthy gastric cancer patients infected with H. pylori. In relation to the genes associated with H. pylori pathogenesis, the presence of genes such as cagA, hopQI, hopQII and so on is used, and PCR of a part of these genes amplified fragments of different lengths. One of the less-studied cases is the association of two or more pathogenic genes simultaneously with H. pylori. In this research, the frequency of disease and healthy individuals who are infected with H. pylori and have two genotypes cagA and hopQI at the same time, was examined. In order to diagnose H. pylori-infected individuals in healthy and gastric cancer patients, after PCR of glmM gene, PCR product electrophoresis on agarose gel was used. For this purpose, gastric tissue biopsy was used in patients and saliva was used in healthy individuals. For this purpose, 100 gastric biopsy samples were collected from patients with gastric cancer and 100 saliva samples from healthy individuals. According to the data, there is a significant relationship between the simultaneous presence of two genes cagA and hopQI and gastric cancer. In patients, 45.3% showed both genotypes, while in healthy individuals only 10.5% have this genotype and other healthy but infected with H. pylori (90.8%) do not have this genotype. To be. No report was observed on the simultaneous study of cagA and hopQI genes. No report was observed regarding the simultaneous study of cagA and hopQI genes.